Pembelajaran Konstruktivis: Gagasan dan Prinsip Dasar serta Aplikasinya dalam Pendidikan Agama Katolik - Stefhanus Hanny Pangemanan (ECCE: Jurnal Pendidikan Pastoral Kateketik, 2025)
Learning Theory of Constructivism has become an integral part in the implementation of curriculum in the learning process on classroom, including in the subject of Catholic Religious Education. Published studies due to the application of Constructivism-based learning in Catholic Religious Education seem to be lacking. Using the literature review method, this article intends to explore the basic ideas and principles of constructivist learning, its significant implications and at the end of the article propose its applications in Catholic Religious Education learning.